Islamic Education Teachers Roles in Muslim Minority Schools: Peran Guru Pendidikan Agama Islam di Sekolah Minoritas Islam - Yusranida Hidayati; Salminawati Salminawati; Zaini Dahlan (Academia Open, 2026)
General Background: Islamic Religious Education in multicultural schools requires contextualized pedagogical practices that accommodate religious diversity while sustaining Islamic values. Specific Background: At SMKS and SMAS Pencawan Medan, where Muslim students constitute a minority, Islamic Education teachers confront limited instructional time, generational gaps, digital literacy disparities, and the necessity to maintain interreligious harmony. Knowledge Gap: Previous studies have predominantly addressed religious moderation and teacher professionalism in Muslim-majority contexts, with limited in-depth exploration of teachers’ lived experiences, cross-religious interactions, and comparative analysis within Muslim minority secondary schools. Aims: This study aims to analyze the roles, personal and professional experiences, interaction patterns, challenges, and institutional differences shaping Islamic Education practices in minority settings. Results: Using a qualitative phenomenological approach through observation, in-depth interviews, and documentation, the findings reveal that teachers function as spiritual mentors, moral educators, social mediators, and facilitators of universal values. In SMKS, the teacher demonstrates strong spiritual exemplarity and persuasive guidance, whereas in SMAS, the teacher adopts technology-based pedagogical innovation and dialogic learning. Interaction patterns are characterized by humanistic, inclusive, and empathetic communication, fostering tolerance and religious moderation. Novelty: The study proposes an integrated model of Islamic Education teacher professionalism that unites spiritual, social, pedagogical, and technological dimensions within Muslim minority schools. Implications: These findings contribute to contextual Islamic education discourse and provide a framework for developing adaptive, inclusive, and technologically responsive Religious Education in plural educational environments. Highlights• Demonstrates multidimensional educator functions within plural secondary institutions.• Identifies comparative distinctions between vocational and general school contexts.• Formulates an integrated professionalism framework combining spiritual guidance and digital pedagogy. KeywordsIslamic Religious Education; Muslim Minority Schools; Teacher Professionalism; Religious Moderation; Multicultural Education